2010
DOI: 10.1093/pcp/pcq180
|View full text |Cite
|
Sign up to set email alerts
|

The R-R-Type MYB-Like Transcription Factor, AtMYBL, is Involved in Promoting Leaf Senescence and Modulates an Abiotic Stress Response in Arabidopsis

Abstract: Functional analysis of a putative novel transcription factor Arabidopsis MYB-like protein designated AtMYBL, which contains two predicted DNA-binding domains, was performed. The physiological role of the R-R-type MYB-like transcription factor has not been reported in any plant. Analyses of an AtMYBL promoter-β-glucuronidase (GUS) construct revealed substantial gene expression in old leaves and induction of GUS activity by ABA and salt stress. AtMYBL-overexpressing plants displayed a markedly enhanced leaf sene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(58 citation statements)
references
References 35 publications
1
56
0
1
Order By: Relevance
“…strain WDL1 (6). Up-and downregulation of membrane proteins have been previously associated with a stress response (60,62). As discussed by Breugelmans et al (6), linuron exposure appears to induce a stress situation in Variovorax.…”
Section: Resultsmentioning
confidence: 86%
“…strain WDL1 (6). Up-and downregulation of membrane proteins have been previously associated with a stress response (60,62). As discussed by Breugelmans et al (6), linuron exposure appears to induce a stress situation in Variovorax.…”
Section: Resultsmentioning
confidence: 86%
“…The putative protein (AtMyb2) encoded by AtMYB2 has 274 amino acids, a molecular mass of 32 kDa and a putative DNA binding domain that shows considerable homology to plant MYB-related proteins, such as maize C1. In addition to this, Zhang et al (2011) reported that AtMYBL functions in the leaf senescence process, and thus modulates an abiotic stress response in Arabidopsis.…”
Section: Abiotic Stressmentioning
confidence: 83%
“…In contrast, several probe sets putatively related to ABA and ethylene biosynthesis were induced in Gifu B-129 roots, where the down-regulation of genes probably involved in auxin and cytokinin response or biosynthesis was also observed. In Arabidopsis , the expression of the senescence-related AtMYBL TF was induced by ABA [74]. In turn, the overexpression of AtMYBL increased the levels of the Senescence-related gene 1 ( SRG1 ), which was reported to increase in senescent organs and hence, it was proposed as a marker for senescence in that model plant [75].…”
Section: Resultsmentioning
confidence: 99%